Implementasi Program Sanitasi Berbasis Masyarakat di Kecamatan Kasemen Kota Serang - Jessica Lofty; Rethorika Berthanilla; Ahmad Sururi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The complexity of the problems, such as the uneven placement of water storage infrastructure, low public awareness of healthy living behavior, less than optimal socialization of the companion team, and weak coordination between DPOs are some of the problems that concern this study. The purpose of this study is to discuss how the implementation of the Sanimas Program in Kasemen District, Serang City and what the inhibiting factors are. The study used a qualitative descriptive approach with data collection techniques through interviews with eight informants and data analysis through the data classification process (coding data), then the results of this data classification were made labels (labeling) and then the categories were arranged. The results showed that in general the implementation of the Sanimas Program in Kasemen District, Serang City was still not successful and running optimally. This is due to unequal access to clean water, lack of community involvement and the absence of local regulations. As for the inhibiting factors from an internal perspective, namely the inadequate quantity of human resources, a lack of coordination between interested parties, and from an external perspective, it includes the socio-cultural factors of society and the geographical conditions of the environment.